PENERAPAN PENDEKATAN OPEN-ENDED UNTUK MENINGKATKAN PENALARAN MATEMATIK SISWA SMP - Indri Herdiman (Jurnal Edukasi dan Sains Matematika (JES-MAT), 2017)
AbstractThis study aims or determining whether the achievement and improvement of mathematical reasoning of junior high school students who learn using open-ended approach is better than using conventional learning. The research conducted was experimental research. The population in this study was all junior high school students in Kabupaten Bandung Barat. While the samples were taken two classes VIII from one grade, where class VIII B became experimental class and class VIII A became the control class . The instrument used in the research was in the form of five essay tests that measure students' mathematical reasoning. To know the improvement of student's mathematical reasoning before and after learning activity, normalized gain calculation was done, then data of pretest and postes result were processed by normality, homogeneity and difference average tests. Based on the analysis of the data resul processing in this study, it could be concluded that the achievement and improvement of mathematical reasoning among students who learn using open-ended approach was better than using conventional learning.Keywords: Open-Ended Approach, Mathematical Reasoning